2021
DOI: 10.1002/fsn3.2369
|View full text |Cite
|
Sign up to set email alerts
|

Study on relationship between bacterial diversity and quality of Huangjiu (Chinese Rice Wine) fermentation

Abstract: Huangjiu (Chinese rice wine) is brewed in an open environment, where bacteria play an important role during the fermentation process. In this study, bacterial community structure and composition changes in the fermented mash liquid of mechanized Huangjiu, well‐fermented manual Huangjiu (wines of good qualities), and poorly fermented manual Huangjiu (wines of poor qualities: spoilage, high acidity, low alcohol content) in different fermentation stages from Guyuelongshan Shaoxing Huangjiu company were analyzed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The species and abundance of microorganisms in different fermented mash were significantly different due to the different types and dosage of wheat Qu . The preliminary study of our laboratory found that there were more bacterial species in well-fermented manual Huangjiu, while the bacterial species in mechanized Huangjiu were relatively few ( Xie et al, 2021 ), and the quality of fermented mash was directly related to the content of Lactobacillus .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The species and abundance of microorganisms in different fermented mash were significantly different due to the different types and dosage of wheat Qu . The preliminary study of our laboratory found that there were more bacterial species in well-fermented manual Huangjiu, while the bacterial species in mechanized Huangjiu were relatively few ( Xie et al, 2021 ), and the quality of fermented mash was directly related to the content of Lactobacillus .…”
Section: Resultsmentioning
confidence: 92%
“…The wheat Qu of manual Huangjiu is naturally cultivated and mixed with pure breeds. Due to the different types and dosages of wheat Qu , there are significant differences in the types and abundance of microorganisms in different fermented mash ( Xie et al, 2021 ), resulting in differences in metabolic pathways between manual Huangjiu and mechanized Huangjiu in the post-fermentation stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA extraction and sequencing were performed according to Xie, GF method (Xie et al., 2021). A linear relationship was established between the sequencing data and flavor substances by partial least squares regression.…”
Section: Methodsmentioning
confidence: 99%